Conceptualizing middle leadership within the South African schools’ context: a semi-systematic review - Mahome, Michael Moreti; Letuma, Motsekiso Calvin (Frontiers in Education, 2025)
Globally, there is currently no shared or decided-upon definition of middle leadership, and South Africa is no exception. This study aimed to identify and analyze empirical peer-reviewed articles on middle leadership to understand how middle leaders are defined within the South African context and propose an operational definition. The search was restricted to South African full-text English-language literature published in the last 20 years, 2004–2024. To minimize selection bias, consistent inclusion and exclusion criteria were applied following the Spar-4-SLR protocol, resulting in a total of 10 articles included for review. A semi-systematic review was conducted using Google Scholar, ERIC, and DAOJ. Thematic analysis was employed to analyze the identified articles, using NVivo 15.2. Consequently, the following three findings emerged that are presented as themes: (1) Middle leadership is conceptualized through various lenses characterized by certain similarities and connections; (2) Middle leaders operate as school managers and classroom teachers; (3) The enactment of middle leadership includes teaching and learning managers, curriculum managers, and the monitoring and controlling of teachers’ work. This study demystifies the confusion of the position, albeit being clearly defined within the South African education policy documents. Presents an operational definition suitable for the South African context and calls for more South African studies in this field to realize a consensus definition of middle leadership as a distinct theoretical lens.